Alexis de Tocqueville, luces y sombras de un autor ambivalente. A propósito del libro de la profesora María José Villaverde Rico, Tocqueville y el lado oscuro del liberalismo - Usategui Basozabal, Elisa (EUNOMÍA. Revista en Cultura de la Legalidad, 2023)
The purpose of this work is to establish a dialogue with Professor María José Villaverde Rico about the thought of Alexis de Tocqueville through the analysis of the main ideas of his book Tocqueville y el lado oscuro del liberalismo. Thus, on the one hand, Tocqueville’s position regarding liberalism is investigated, that is, his notion of citizenship, the role of the State in the economy and education and his social approaches. At the same time, the place given to women in democratic societies and its markedly colonialist political positions on the question of Algeria and the abolition of slavery are questioned. However, despite the existence of a dark side in our author, his reflections on democracy are essential today to work on democracy as a problem to think about.